Evaluation of Sinapic Acid on STZ-induced Depression in Diabetic Wistar Rats - Pawar, Shubhangi; Shinde, Sheetal; Khapare, Ekta; Bacchav, Rishikesh (Indian Journal of Pharmaceutical Education and Research, 2023)
Objectives: Presently, diabetes is a major chronic metabolic abnormality characterized by sustained hyperglycemia. Diabetic neuropathy, encephalopathy, diabetes induced anxiety, depression is common life-threatening complications in which hyperglycemia mediated oxidative stress plays major role in pathogenesis. Sinapic acid is a phenolic acid, reported with anti-inflammatory, antioxidant, anti-bacterial, anti-tumor, anxiolytic activity and also it is proven to be neuroprotective in diabetic neuropathy. Materials and Methods: This study was designed to evaluate anti-depressant activity of Sinapic acid on STZ induced diabetic Wistar rats. Animals were divided into six groups (n = 6). Diabetes was induced by single dose of STZ injection 55 mg/kg i.p. and sinapic acid was administered orally (5, 10, 20 mg/kg) after confirmation of hyperglycemia for next 4 weeks. Behavioural parameters like tail suspension test and forced swim test, antioxidant enzymes (SOD, GSH), oxidative stress (NO, MDA), total protein level were estimated and morphology of brain was examined histopathologically. Results: The results suggested that sinapic acid have decreased duration and percent of immobility, oxidative stress and increased antioxidant enzymes and total protein level. Morphological damage and neuronal degeneration in brain tissue was normalised by Sinapic acid. Conclusion: Thus, Sinapic acid shows antidepressant activity in diabetes induced depression.
Keywords: Sinapicacid; STZ; Diabetes; Depression